Cleft Lip and Palate Surgery: Prevalance of Intraoperative Airway Complications in a Tertiary Center in Nepal - Thapa, Ajay Singh; Yadav, Rajesh Kumar (Birat Journal of Health Sciences, 2020)
Introduction: Cleft lip and palate is one of the most common congenital malformations. Different syndromes have been described in association with cleft lip and palate, some of which have considerable anesthetic implications, and many involve potential airway problems. Objective: This study aimed to find the incidence of airway complications during cleft surgeries. Methods: The descriptive cross sectional study was conducted in College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal over a period of one year from March 2017 toFebruary2018. All the 146 patients received general anesthesia. The parameters studied were incidence of difficult mask ventilation, difficult intubation, laryngospasm, bronchospasm, aspiration of blood and secretion. Univariate analysis of demographic and occurrence of complications was done. Results: A total of 146 patients underwent cleft surgery over the study duration out of which 42(28.76%) were female and 104(71.23%) were male. Isolated cleft lip was seen in 104 (71.23%) patients among whom 42 (28.76%) had right sided, 50 (34.24%) had left sided and 12 (8.21%) had bilateral cleft lip. Isolated cleft palate was seen in 12 (8.21%) patients. Combined cleft lip and palate was seen in 30 (20.54%) patients. Prevalence of difficult mask ventilation, difficult laryngoscopy, difficult intubation, incidence of bleeding during intubation, bronchospasm and post extubationlaryngospasmwere4 (2.73%), 11 (7.53%), 6 (4.10%), 2 (1.36%), 2(1.36%) and 4(2.73%). Conclusion: In cleft repair surgeries, difficult laryngoscopic view is the most common problem followed by difficult intubation and difficult mask ventilation. Complications like laryngospasm, bronchospasm and laryngoscopy related bleeding are not uncommon. Vigilant perioperative preparation and continuous monitoring is essential to prevent complications during cleft repair surgery in paediatric patients.